European Union in Promotion of Global Governance in the UN System - A. S. Boyashov (Международная аналитика, 2022)
Having evolved since the 1990s into a political and ideological concept, global governance has become one of the priorities of the program documents of EU states and institutions, today formulated as “rules-based order”. A distinctive feature of this concept is the “blurring” of interstate interaction on the world stage in favor of non-state and supranational interaction. Under global governance, there is allegedly no hierarchy between state actors and nonstate or supra-state actors. This article critically examines this thesis with the help of the sociological theory of diff erentiation. According to diff erentiation theory, the state does not remain on the sidelines of global governance but takes the lead in the hierarchy of levels of world politics. The fi nal part of the article deals with the principles of EU coordination in the UN system. To promote ideas of global governance, the EU aims at major reform of the UN through intertwining intergovernmental interaction with nongovernmental interaction. This model is used especially often when non-core issues (e.g., human rights or climate in the Security Council) are considered in a UN body, allowing for broader participation in negotiations and, from a strategic perspective, a revision of the UN Charter. The main conclusion of the article is that the EU’s actions in the UN system refute the position of global governance that there is no hierarchy between the interstate and supranational levels of world politics. Despite the active promotion of global governance by the EU states, the EU itself is based on interstate coordination and a rigid hierarchy among states, as well as between states and nongovernmental actors.